Pelatihan penyusunan artikel ilmiah bagi guru sekolah dasar di Kecamatan Marpoyan Damai Pekanbaru - Dea Mustika; Siti Quratul Ain (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
This activity is motivated by the lack of understanding and ability of elementary school teachers in the preparation of scientific articles. Many teachers are still reluctant to publish research results on the grounds that they do not understand the guidelines for preparing scientific articles. This is what underlies the need to carry out this service activity with the aim of helping elementary school teachers in compiling scientific articles so that later teachers can publish articles that have been made in journals or mass media. Community service activities were carried out in January 2020 at the SDN 193 Pekanbaru teacher council room. The method used is divided into two stages, namely the delivery of material and assistance for teachers who want to compile scientific articles according to their reports. With this service activity, it can provide new concepts of knowledge for teachers so that they can compile scientific articles, especially from the results of research that has been done.